The organization trust and organization politic in the Royal Malaysia Customs Department Kuching / Nor Hidayah Ismail - Ismail, Nor Hidayah (2013)
This study aims to determine the level of Organizational Trust and Organizational Politic in The Royal Malaysia Customs Department in Kuching. The study covers at The Royal Malaysia Customs Department in Petra Jaya Kuching, through the random sampling of 100 employees from various levels of education and categories. A questionnaire was distributed to the groups mentioned and the data was analyzed manually and transformed into figures using SPSS 16.0. The findings revealed that most of the respondents are believe that their organization can be trust and no politic issues are being use in order to gain power, promotion and pay raises within the department. The people perspectives that within the department the organization can’t be trusted are denied because there is no way the organization is high in politic approaches. It should be seen that the department are competent and using the proper ways to manage the promotion and pay raises. That’s why, the performance of the employees should be increase by motivated them with proper rewards.